Penerapan Model Pembelajaran Snowball Throwing Berbantuan Kode SMILES pada Materi Hidrokarbon Terhadap Hasil Belajar Siswa Kelas XI SMA Negeri 5 Palu - Djahir, Ahmad Rifaldi; Walanda, Daud K.; Hamzah, Baharuddin (Universitas Tadulako, 2014)
Snowball throwing learning model is a modification of aquastion technique. This technique is focused on the ability to formulate questions which are combined in a game called snowball throwing. SMILES is a simple chemical notation comprehensive where the scructures of molecules can be found by using ASCII character which representing atom and bond symbol. The study aim is to determine the influence of snowball throwing assisted learning model SMILES code on hydrocarbon material to the learning outcomes of students clas XI in SMA Negeri 5 Palu. This study is experimental with pretest and posttest control group design, in which the samples are students of class XI IPA 2 (n=33) as experimental group while students of clas XI IPA 4 (n=32) as control group. The testing data used t-test statistical analysis one side (right) with pre-requisite test, normality test and homogeneity. The result of data analysis are the score of X1 experiment class is 73.81 with standard deviation is 8.19 while score of X2 control group is 65 with standard deviation is 14.36. Based on testing hypothesis result that tcounted>ttable is 3.05 > 1.67 with significance level 0.05 and confidence level = 63. The results show that H0 is rejected and H1 is accepted then it is concluded that the application of Snowball Throwing assisted learning model SMILES code on hydrocarbon material positively influence to the learning outcomes of students class XI in SMA Negeri 5 Palu.